The Effectiveness of a Treatment Program in Decreasing the Psychological Stressors and Improving Self-Concept of Philadelphia University Students - Sanaa N. Al-Khawaldeh; Asmaa N. Al- Khawaldeh (Sultan Qaboos University, 2018)
The current study aimed to identify the effectiveness of a treatment program in decreasing the psychological stressors and improving self-concept of Philadelphia University students. The study population consisted of all students of the Faculty of Arts at Philadelphia University for the academic year 2015-2016. The psychological stressors and the self-concept measures were applied as a pre-test on 45 students, who wished to participate in the program.The study sample was selected from students who obtained high scores on the psychological stressors scale, and students who obtained low scores on the self-concept scale, which amounted to 30 students, who were divided randomly into two groups: the experimental group, which included 15 students who received the treatment program, and the control group, which included 15 students who did not receive the treatment program. Multivariate Analysis of Covariance was used to answer the first and the third questions, and the T-test of the associated samples was used to test the significance of differences between the two groups and answer the second and the fourth questions. The results of the statistical analysis indicated that there were statistically significant differences at the level of significance (α ≤ 0.05) between the experimental and the control groups on the post-test of both the stressor and the self-concept scales due to the effectiveness of the treatment program that has been applied to the experimental group.